Optimasi Formula Sediaan Lip Cream Sari Buah Stroberi Kering (Fragaria x ananassa) dan Minyak Jarak dengan Metode Simplex Lattice Design - Risyafa, Jihan; Suprapto, Suprapto (Journal of Pharmaceutical and Sciences, 2026)
Strawberries (Fragaria x ananassa) contain striking red anthocyanin pigments that can serve as natural colorants for lip cream preparations and also as antioxidants. The emollient properties of castor oil can rehydrate dry skin, allowing it to function as a moisturizer for the skin and lips. This study aims to obtain the optimal formula for lip cream combining strawberry fruit strawberry juice powder as a natural colouring agent and castor oil as a moisturizer. Both ingredients were optimized using Design Expert V13 Simplex Lattice Design method, resulting in 5 formulas in 8 runs. The lip cream preparations were evaluated based on organoleptic, homogeneity, pH, viscosity, adhesion, spreadability, irritation, hedonic, and antioxidant tests to obtain the optimal formula. Verification of the optimal formula was carried out to ensure the validity of the results. The results of the study obtained an optimal formula with a composition of 33.15 g of strawberry juice powder and 13.85 g of castor oil with a desirability value of 0.524. The optimal formula produced a pH response of 5.6; viscosity of 17686.7 cP; adhesion of 4.06 seconds; spreadability of 6.57 cm; hedonic properties in terms of colour, aroma, and spreadability of 4.7, 4.7, and 4.8, respectively; and antioxidant activity with an IC₅₀ value of 21.31 ppm. The results of the verification formula on the parameters of pH, viscosity, adhesive power and spread power did not show significant differences.